Generation of fibrolytic enzymes using paddy husk as substrate and identifying corresponding crop residues for the generated fibrolytic enzymes* - SARAVANAKUMAR, S; VALLI, C; BALAKRISHNAN, V (The Indian Journal of Animal Sciences, 2013)
A study was carried out to produce cellulase and xylanase using paddy husk as substrate and to match the enzymes produced with sorghum stover, paddy straw and sugarcane tops. For optimization of conditions for growth of Trichoderma viridae in paddy husk, the experiment was conducted in a factorial design in nine replicates, with 2 pH levels (5, 7), 2 moisture levels (50 and 70%) and 3 incubation periods (10, 15 and 20 days). Cellulase and xylanase activity declined as the incubation period increased irrespective of pH and moisture level. Based on the results, the optimum conditions identified was 10 days incubation, pH 5 and moisture of 50%. The level of enzymes for sorghum stover, paddy straw and sugarcane tops identified for the in vitro degradability study considered practical feasibility of inclusion of Trichoderma viridae fermented paddy husk to crop residues. First the level of crude enzyme extract to be supplemented was identified and next the possibility of supplementing Trichoderma viridae fermented paddy husk to the crop residues in lieu of crude enzyme extracts was examined. It was concluded that 2.03 U (Units) of cellulase and 2.73 U of xylanase was required per gram of paddy straw or sorghum stover and 3.05 U of cellulase and 4.10 U of xylanase was required per gram of sugarcane tops to augment their degradability. Supplementation of Trichoderma viridae fermented paddy husk as such to the crop residues was beneficial compared with extracting enzymes and supplementing.